Ekstraksi dan Identifikasi Senyawa Fitokimia Bunga Telang (Clitoria ternatea) - Indriyani Indriyani (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2026)
Butterfly pea flower (Clitoria ternatea) is a herbal plant known for its health benefits due to the presence of various bioactive compounds. This study aimed to identify the phytochemical compounds contained in butterfly pea flowers through an extraction method using ethanol as the solvent. The flower samples were dried and homogenized using a homogenizer until a fine powder was obtained. The powder was then macerated with 96% ethanol for 2 × 24 hours to obtain a concentrated extract. The resulting extract was analyzed through qualitative phytochemical screening to identify the presence of qualitative phytochemical screening to identify the presence of secondary metabolites, including alkaloids, flavonoids, saponins, tannins, phenols, steroids, and terpenoids. The results showed that butterfly pea flower extract positively contained flavonoids, saponins, tannins, phenols, steroids, and terpenoids. The presence of potential as a natural material with biological activity, particularly as a source of antioxidants. This study is expected to provide supporting data for the development and utilization of butterfly pea flower in the health sector and natural-based products.